Comprehensive analysis of the codon usage patterns in the polyprotein coding sequences of the honeybee viruses - Aktürk Dizman, Yeşim (Frontiers in Veterinary Science, 2025)
Honeybee viruses (HVs) are some of the most significant pathogens affecting these insects and are commonly found in beehives across the globe. This viral infection leads to substantial economic losses in the beekeeping industry. To understand the evolution and adaptation of HVs, such as Acute Bee Paralysis Virus (ABPV), Kashmir Bee Virus (KBV), Chronic Bee Paralysis Virus (CBPV), and Sacbrood Virus (SBV), a detailed analysis of codon usage bias (CUB) was conducted, as no prior studies on this topic had been reported. Analysis of nucleotide content and RSCU revealed that the polyprotein coding sequences of the four HVs were rich in A/U nucleotides, with the third base of synonymous codons predominantly A/U. The polyprotein coding sequences showed a higher effective number of codons (ENC) value, suggesting lower CUB. The ENC plot, PR2 plot, and neutrality analyses indicated that natural selection predominantly shapes the codon usage pattern of polyprotein coding sequences, with minimal influence from mutation pressure. Analyses of the codon adaptation index (CAI) and relative codon deoptimization index (RCDI) showed a strong relationship between HVs and their hosts. These findings could offer essential insights into the overall codon usage patterns of HVs and help in understanding the mechanisms that influence codon usage and genetic evolution in HVs.